Fever-range hyperthermia promotes cGAS-STING pathway and synergizes DMXAA-induced antiviral immunity. (1st January 2021) - Khan, Inam Ullah; Brooks, Gabriel; Guo, Nina Ni; Chen, Junsong; Guo, Fang
Abstract: Background: Fever-range hyperthermia or fever-range temperature (hereafter FRT) improves survival and shortens disease duration in microbial infections. However, the mechanisms of these beneficial effects still remain elusive. We hypothesized that FRT might enhance cell responsiveness to infections by promoting cGAS-STING signaling to cause enhanced production of IFN-β. Objective: To investigate the effect fever-range hyperthermia on cGAS-STING pathway. Methods: RAW 264.7 and cGAS -/- RAW 264.7 cells, stimulated with 5μg/ml herring testis DNA (htDNA), were heated to 39.5°C and analyzed for the expression of cGAS, STING, IFN-β, and the synthesis of cGAMP and IRF3 phosphorylation. In vivo, wild type C57BL/6J mice were subjected to whole body hyperthermia (WBH) at 39.5°C. The mice were then challenged with influenza virus and analyzed for antiviral response in term of IFN-β expression, body weight and survival. Results: We found that 39.5°C FRT upregulated the expression of cGAS and STING, and induced the synthesis of cGAMP and production of IFN-β in htDNA-transfected RAW 264.7 cells more potently as compared to 37°C. Moreover, FRT+DMXAA-treated cells were better protected from vesicular stomatitis virus (VSV)-induced cytotoxicity in vitro in contrast to the nonprotected control (no FRT and DMXAA) or DMXAA treatment alone. In vivo, FRT at 39.5°C, co-administered with DMXAA, significantly induced the expression of IFN-β, showed reduced weight loss mice and exhibited 25% more survival over the course of 14 days as compared to DMXAA treated mice 37°C. Conclusion: We conclude that fever-range hyperthermia promotes cGAS-STING pathway to cause increased expression of IFN-β and mediate its antiviral effects.